Institutional Matrix of the Social State and Democracy in Russia - Bessonova, Olga (Journal of Economic Sociology, 2018)
The purpose of this article is to show that, at the present stage, the institutional matrix of contractual razdatok provides conditions for the social state and democratic development of Russia, and to refute the myth that only market institutions are needed for the development of democracy. The new integralinstitutional paradigm radically changes the view of mankind’s evolution which is regarded as the development of institutional forms of the market and razdatok. At the local level, the market and razdatok are “equal hands” of the state, which equally regulates markets and also distributes resources on the basis of state orders. The reality of the 21st century consists not in the opposition of market and razdatok economies, but in the synthesis of market institutions and razdatok. And so, the dilemma is not a plan or a market, not socialism or capitalism, but a quasi-market or contractual razdatok. Outwardly, both models look similar; resources are distributed on a competitive basis through state orders and contracts are concluded with legal guarantees. However, extractive synthesis creates a quasi-market which leads to limited access orders and protects the monopolistic public rent acquisition by a narrow group of individuals with personal interests, whereas the contractual razdatok model relies on inclusive institutions which ensures the inclusion of all social groups in the process of social development through the redistribution benefits of a market economy. Inclusive synthesis in the form of contractual razdatok gives rise to a new institutional matrix of the social state and democracy for the economy, with both market and distributional prior development. As a result, economic rationality, and not ideological opposition, will determine the use of market or distributing relations through their combination in different forms. The economic course based on an institutional matrix of contractual razdatok in modern Russia will not be a return to the Soviet authoritarian past but will serve as an effective engine for overcoming the systemic crisis and the establishment of a democratic open access order